Memory, Identity and Otherness in Rhea Galanaki’s Novel "The Life of Ismail Ferik Pasha: Spina Nel Cuore" - Neli Popova (Zeszyty Cyrylo-Metodiańskie)
Rhea Galanaki is widely regarded not only as a prominent contemporary Greek author but also as a key figure in the revival of the Greek historical novel, alongside writers such as Maro Douka, Alexis Panselinos, and Nikos Themelis. This new iteration of the historical novel, as articulated by Vangelis Hadjivassiliou, refrains from instrumentalizing the dichotomy of Self and Other to valorize the ‘own’ at the expense of the ‘other.’ Instead, it often explores the Other as an intrinsic element of the Self, a theme exemplified in Galanaki’s work. Through this nuanced approach to the past, the conventional stereotypes underpinning national identity are subjected to critical reexamination. This paper investigates how Galanaki’s novel addresses the interrelated themes of identity and Otherness, focusing on the manifestations and functions of memory and the recurring motif of return. Rather than seeking to delineate a fixed or immutable core of the Self, the analysis traces the protagonist’s journey toward reconciling polarized aspects of their existence. The study situates the relationship between identity, memory, and Otherness within the theoretical framework of Paul Ricoeur’s concept of identity, offering a deeper understanding of these interconnections in the novel. Original title in Bulgarian: Памет, идентичност и другост в романа „Житието на Исмаил Ферик паша: Spina nel cuore“ на Реа Галанаки.